Proximate analysis and shelf-life studies of Yoghurt Chia (Salvia Hispanica L.) pudding / Noranisa Zainal Abidin ... [et al.]. - Zainal Abidin, Noranisa; Md Japilus, Siti Jameelah; Kassim, Ahmad Fikri; Miswan, Syafiq; Mohd Nooh, Hisham (Universiti Teknologi MARA, Negeri Sembilan, 2024)
Consuming Salvia hispanica L., also known as chia seed, has been linked to studies that suggest positive impacts on individual health outcomes. This study was sought to examine the proximate composition and energy value, as well as the shelf life the formulated yoghurt chia pudding in different storage temperatures during 20 days of storage. The sample was evaluated for proximate analysis (moisture, protein, fat, ash, fibre, and carbohydrate) and the energy value using method of drying method, Kjeldahl, Soxhlet, dry ashing, acid and alkali digestion, and the arithmetic difference method. The shelf-life analysis was also evaluated for the effects of the storage temperature on the microbial analysis and pH across 20 days. The results obtained from this study indicated that the formulated yoghurt chia pudding has an energy value of 134.95 Kcal/100g and contained high fibre, carbohydrate, protein, and fat content with a value of 9.01%, 9.85%, 6.06%, and 7.92%, respectively, which were primarily imparted by the chia seeds’ excellent nutritional composition. The lower count level of mould and yeast (CFU/mL) recorded for the yoghurt chia pudding sample in both chilled and frozen temperature throughout the storage period signifies the antimicrobial properties which shows a zone of inhibition of 8 mm diameter against the gram-positive bacteria (S. aureus) but less effects on the gram-negative bacteria (E. coli). For all storage temperatures, a gradual fall in the pH of yoghurt chia pudding over time can be observed. To sum up, the study demonstrated that chia seeds improve nutritional value, shelf life, and also possess antimicrobial properties. Thus, the consumption of yoghurt chia pudding as a healthy snack or meal alternative may support satiety or a sense of fullness, enhance digestive health, and offer sustained energy, making it a perfect choice for active people or a quick healthy snack for everyone.